ARV2V: Attack resistant vehicle to vehicle algorithm, performance in term of end-to-end delay and trust computation error in VANETs - Rehman, Mujeeb Ur; Ahmed, Sheeraz; Khan, Sarmad Ullah; Begum, Shabana; Ishtiaq, Atif (2018 International Conference on Computing, Mathematics and Engineering Technologies (iCoMET), 2018)
Making cities smarter and well equipped in communication prospective VANETs plays significant role. These days VANETs are quickly maturing and emerging technique in the field of communication technology build upon on the IEEE 802.11p standard proposed for DSRC among vehicles and following IEEE 802.11a/b/g standard for RSUs and vehicle communication. VANETs make the existence of ITS possible in WAVE through dissemination of vital FSAMs among vehicles to avoid any misfortune. The FSAMs basically consist of information about traffic situation, malicious nodes penetration, loss of information etc. However, due to high mobility environment vehicles distance among nodes varies which can also affect the link and delay or loss of information may also take place. So, absolute protocols in VANETs for desire output and data delivery on perfect time is still a challenging job. In our research work we tried to design a routing scheme, which provides better performance than the existing schemes like Trust and Logistic Trust. We compare our design scheme ARV2V in term of performance metrics, which are EED and TCE with Trust and LT techniques. In VANETs system it is important to receive data on time with less delay and minimal error to handle disastrous circumstances wisely. In our research paper we analyzed EED and TCE in Trust, LT and in our scheme ARV2V. We observed from simulation results that our scheme is much efficient than Trust and LT. From the comparison analysis our scheme ARV2V in term of performance metric TCE is 11.6% and 7.3% more efficient than LT and Trust schemes respectively, while Trust scheme is 4.3% efficient than LT. From EED comparison we observed that ARV2V 57.6% more efficient than Trust and 5.2% than LT, also Trust schemes faced 52.4% more delay than LT.